Lack of reduction in buprenorphine injection after introduction of co-formulated buprenorphine/naloxone to the Malaysian market - Bruce, R.D.; Govindasamy, S.; Sylla, L.; Kamarulzaman, A.; Altice, F.L. (2009)
Background: Diversion of buprenorphine (BPN) has been described in settings where it is legally prescribed and has resulted in increasing concern. To address this concern, co-formulation of buprenorphine/naloxone (BPN/NLX) replaced buprenorphine alone in Malaysia in December 2006. Methods: To assess the significance of BPN/NLX introduction, 41 BPN/NLX injectors in Kuala Lumpur, Malaysia were recruited using a modified snowball recruitment technique. Results: In January 2007, all subjects had previously injected BPN alone. During the transition from injecting BPN alone to co-formulated BPN/NLX, the mean daily BPN injection dose increased from 1.88 mg (range 1.0-4.0 mg) to 2.49 mg/day (p .001). Overall, 18 (44) subjects increased their daily amount of injection while 22 (54) had no change in dose; only one subject reduced the amount of injection. Development of opioid withdrawal symptoms was the primary outcome, however the only symptom that was significantly associated with BPN/NLX dosage was the report of stomach pains (p = .01). In logistic regression analysis, the development of opioid withdrawal symptoms was associated with increased benzodiazepine injection and increased syringe sharing. Conclusion and Scientific Significance: These data suggests that the introduction of BPN/NLX did not reduce injection related risk behaviors such as syringe sharing and was associated with increased benzodiazepine use. Evidence-based approaches to treat BPN injection are urgently needed.